Do fencers require a weapon-specific approach to strength and conditioning training? - Turner, A. N.; Bishop, C. J.; Cree, J. A.; Edwards, M. L.; Chavda, S.; Read, P. J.; Kirby, D. M. J. (The Journal of Strength and Conditioning Research, 2017)
There are 3 types of weapons used in Olympic fencing: the épée, foil, and sabre. The aim of this study was to determine if fencers exhibited different physical characteristics across weapons. Seventy-nine male (n = 46) and female (n = 33) national standard fencers took part in this study. Fencers from each weapon (male and female), i.e., épée (n = 19 and 10), foil (n = 22 and 14), and sabre (n = 13 and 10), were (mean ± SD) 15.9 ± 0.7 years of age, 178.5 ± 7.9 cm tall, 67.4 ± 12.2 kg in mass and had 6.3 ± 2.3 years fencing experience; all were in regular training (~4 times per week). Results revealed that across all performance tests (lower-body power, reactive strength index, change of direction speed, and repeat lunge ability), there was no significant main effect for weapon in male fencers (p = 0.63) or female fencers (p = 0.232), but a significant main affect for gender (p < 0.001). Pairwise comparisons revealed that male fencers scored better during the countermovement jump, change of direction speed, and repeat lunge ability test (p < 0.001). The former findings may be because of similarities in bout intensity and time, movement types (lunging and changing direction), and the need to execute competition actions as explosively as possible. Based on the findings of the present study, it could be indicated that épée, foil, and sabre fencers do not require a weapon-specific approach to strength and conditioning training. Each fencer should target the area they are weakest at, rather than an area that they feel best represents the unique demands of their weapon.